Relegitimizing Halal Food and Beverage Violations: The Role of Brand Ethical Behavior and Perceived Brand Integrity - Wildan Fajar Bachtiar (Universitas Darussalam Gontor, 2025)
This study investigates the relegitimization process for halal food and beverage brands following violations, emphasizing the roles of brand ethical behavior and perceived brand integrity. Using a systematic literature review of 40 relevant articles, the research highlights the challenges faced by brands in rebuilding consumer trust and ensuring compliance with Islamic dietary laws. The findings underscore that halal legitimacy extends beyond regulatory compliance, encompassing ethical transparency and adherence to religious principles, which are essential for consumer trust. The study proposes a conceptual framework illustrating how brand ethical behavior directly enhances halal legitimacy while being mediated by perceived brand integrity. This dual influence emphasizes the need for a holistic strategy, combining ethical actions with efforts to strengthen consumer perceptions of integrity. The insights presented contribute to understanding relegitimization in halal markets and provide actionable guidance for brands aiming to regain consumer confidence and maintain market competitiveness. Future research should empirically validate this framework and explore the cultural nuances influencing the relegitimization process.